Perwujudan good village governance: Perspektif muraqabah dalam Islam - Munir Munir; Saiful Muchlis; Rimi Gusliana Mais (LPMP Imperium, 2022)
This study aims to implement Islamic muraqabah values ​​in financial management in Bana Village, Bontocani District, Bone Regency. This type of research is qualitative by using the paradigm of Interpretive Phenomenology. Data were collected through in-depth interviews, observation, documentation studies, and voice recording devices. The results showed that financial management in Bana Village, Bontocani District, Bone Regency, was based on the principles of Good Village Governance, when viewed at the participatory planning stage, which was not yet effective. The implementation phase, the principles of transparency and budget discipline have been carried out well. Accountability to the community has not provided maximum results. Has not provided a good performance, as evidenced by the misuse of the functions and responsibilities of the BPD involved in handling development projects.